2023
DOI: 10.29333/ejmste/13809
|View full text |Cite
|
Sign up to set email alerts
|

Integrating sustainability in mathematics education and statistics education: A systematic review

Claudia Vásquez,
Ángel Alsina,
María José Seckel
et al.

Abstract: If we are to understand and address today’s social, environmental and economic crises through education, we must introduce education for sustainable development (ESD) into classrooms and approach it from an integrated perspective. In so doing, this study aims to provide an overview of the current status of the still-emerging research agenda on the integration of ESD into mathematical education and statistical education. To this end, we conducted a systematic review of Scopus and Web of Science databases of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Many studies have shown that environmental literacy including conservation attitudes can be developed in schools and universities [40]. If this model is implemented at the university level, the EfSD education program can be used as a conservation program for an area [41]. Sustainable development competencies can be included in the development of academic programs.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that environmental literacy including conservation attitudes can be developed in schools and universities [40]. If this model is implemented at the university level, the EfSD education program can be used as a conservation program for an area [41]. Sustainable development competencies can be included in the development of academic programs.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, in recent years, there has been a specific line of research that connects statistics education with education on sustainable development, showing that statistics education provides tools to understand and respond to real-life problems [23]. In this sense, there is a need to encourage a teaching of statistics that promotes education for sustainable development.…”
Section: The Mtia: An Approach For Addressing the Teaching Of Statist...mentioning
confidence: 99%
“…In this sense, there is a need to encourage a teaching of statistics that promotes education for sustainable development. Under this perspective, ESD is structured with the purpose of teaching statistics, and, in turn, statistics provides a pretext to train in sustainability [23]. However, there is still much to investigate regarding the integration of statistics and sustainability, especially concerning the design of classroom experiences that facilitate the development of sustainability skills in order to properly characterize them.…”
Section: The Mtia: An Approach For Addressing the Teaching Of Statist...mentioning
confidence: 99%
See 2 more Smart Citations